An approach to endodontic surgery as an option to the failure of conventional endodontic treatment (Research, Society and Development, 2023)
This research is based on the concern of evaluating the criteria used to approach endodontic surgery in cases where conventional endodontic treatment is not effective in resolving the problem. In the meantime, the objective of this article was to carry out an analysis of when it is really necessary to adopt a surgical and unconventional approach. This is a narrative review of the literature, developed through searches for publications obtained in the databases: PubMed, SciELO, Scopus, LILACS and Google Scholar. The descriptors used were: abscess, retreatment, fistula and inflammation. At the end, we selected 34 publications to compose the study. Through the analysis of the articles, it was possible to demonstrate that periapical surgery is an alternative for preserving the tooth in the oral cavity in cases where periapical inflammation is persistent even after conventional root canal treatment. It is concluded, therefore, that greater care with oral health and good planning for the indication of surgical intervention is essential.